2016
DOI: 10.4103/2231-0746.200334
|View full text |Cite
|
Sign up to set email alerts
|

Postsurgical consequences in lower third molar surgical extraction using micromotor and piezosurgery

Abstract: Background:One of the most critical and crucial steps in surgical extraction is cutting the bone or osteotomy, for which many techniques are used, e.g., chisels and mallet, rotary instruments, and ultrasound bone-cutting instruments. If they are not used judiciously, they can be hazardous.Objectives:To assess the efficiency of piezosurgery unit over micromotor while performing surgical extraction of lower third molars by assessing the time taken for the surgery and measuring postoperative parameters such as pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 25 publications
3
12
0
14
Order By: Relevance
“…The rotary procedure showed a greater clinical value of facial swelling compared to the piezoelectric surgery in all the postoperative times, especially at postoperative day 3, which is in agreement with others ( Jiang et al, 2015 ; Mantovani et al, 2013; Mistry et al, 2016 , Sortino et al, 2008 , Troedhan et al, 2011 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The rotary procedure showed a greater clinical value of facial swelling compared to the piezoelectric surgery in all the postoperative times, especially at postoperative day 3, which is in agreement with others ( Jiang et al, 2015 ; Mantovani et al, 2013; Mistry et al, 2016 , Sortino et al, 2008 , Troedhan et al, 2011 ).…”
Section: Discussionsupporting
confidence: 90%
“…There is a great deal of literature ( Arakji et al, 2016 , Badenoch-Jones et al, 2016 , Bartuli et al, 2013 ; Bhati et al, 2010; Bhati et al, 2017 ; Mantovani et al, 2013; Mistry et al, 2016 , Sortino et al, 2008 ) on the relationships between the postoperative complications following extraction of the lower third molars using piezoelectric surgery. However, little has been published ( Basheer et al, 2017 , Chang et al, 2015 , Goyal et al, 2012 , Piersanti et al, 2014 ) regarding patient perceptions on postoperative quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no significance in the values recorded on day 7 and 14, which indicated recovery would be between 3 and seven days concerning trismus. In the rotatory group, values were significantly lower on days 1, 3 and 7, which indicated that recovery would be between 7 to 14 days, which was in accordance with previous authors [18]. The pain was evaluated by asking the patient to score on facial pain scale during the followup.…”
Section: Discussionsupporting
confidence: 87%
“…[14] A similar study stated that males usual lifestyle activities were resumed by four days after surgery, while difficulties due to trismus were resolved after five days post-surgery, but females had greater surgical time than males; average of 30 minutes; the resolution of trismus took a longer time than males. [15] Consistent results were obtained using micromotor and piezosurgery; longer surgical time meant trismus persisted for more number of days; follow-up of trismus for this study was for 15 days. [16] Another study stated that meticulous surgical techniques minimises total surgical time and hence severity of pain, swelling and trismus.…”
Section: Discussionsupporting
confidence: 81%